2018
DOI: 10.1038/s41598-018-31000-9
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent extinction of threat memories: influences of healthy aging

Abstract: Although a substantial progress has been made in recent years on understanding the processes mediating extinction of learned threat, little is known about the context-dependent extinction of threat memories in elderly individuals. We used a 2-day differential threat conditioning and extinction procedure to determine whether young and older adults differed in the contextual recall of conditioned responses after extinction. On Day 1, conditioned stimuli were paired with an aversive electric shock in a ‘danger’ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 91 publications
2
61
0
Order By: Relevance
“…The prevalence of automatic responding is indeed generally associated with addictive, impulsive, and obsessive traits 34 39 , 44 47 . In this sense, the lack of conscious processing that characterizes general transfer could potentially be a marker of vulnerability to maladaptive forms of cue-guided choices 3 . In the case of addiction, for example, although no direct correlation between drug or food forms of addiction and outcome-specific transfer has been reported in literature 48 , 49 , it cannot be excluded that this is instead related to forms of cue-driven choice requiring a lower level of processing, like in the case of general transfer 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of automatic responding is indeed generally associated with addictive, impulsive, and obsessive traits 34 39 , 44 47 . In this sense, the lack of conscious processing that characterizes general transfer could potentially be a marker of vulnerability to maladaptive forms of cue-guided choices 3 . In the case of addiction, for example, although no direct correlation between drug or food forms of addiction and outcome-specific transfer has been reported in literature 48 , 49 , it cannot be excluded that this is instead related to forms of cue-driven choice requiring a lower level of processing, like in the case of general transfer 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In everyday life, environmental cues can anticipate the presence of potential rewards, or punishments, thus biasing choice (i.e., cue-guided choices). Although evidence shows that the mere presence of reward-associated cues can influence individual choice [2][3][4] , the boundary conditions within which this occurs remain unknown. In particular, it is not clear whether the conscious elaboration of such cues is necessary to elicit cue-guided choices 5,6 .…”
mentioning
confidence: 99%
“…With instrumental conditioning, we learn to predict the consequences of a given action, whereas with Pavlovian conditioning we learn to predict the consequences associated with the presence of external cues. Information gathered via such learning processes, even if independently acquired, can be integrated to guide behaviour 24 . An example of this mechanism can be observed in the Pavlovian-to-Instrumental Transfer (PIT) effect, which tests the extent to which a Pavlovian stimulus (S) can drive instrumental responses (R) independently paired with the same or a similar outcome (O).…”
Section: Introductionmentioning
confidence: 99%
“…Threat and safety learning are most commonly assessed by measuring psychophysiological signals of arousal, such as the skin conductance response, which indicate the sympathetic nervous system's defensive response to direct, impending threat. Previous studies investigating threat conditioning in older adults have shown no age‐related differences in older adults' behavioural or psychophysiological differential responses to conditioned stimuli beyond a general reduction in arousal (Battaglia, Garofalo, & di Pellegrino, 2018; LaBar, Cook, Torpey, & Welsh‐Bohmer, 2004; Rosenbaum et al, 2015). However, the absence of behavioural and psychophysiological differences does not necessarily imply the absence of neural differences.…”
Section: Introductionmentioning
confidence: 95%